Forests and Human Health: A Symbiotic Relationship for Greener Pakistan - Amanullah, Amanullah; Khan, Urooj (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2024)
Forests are not merely silent witnesses to the passage of time; they are vital partners in our quest for well-being and sustainability. This article explores the intricate and symbiotic relationship between forests and human health. Covering approximately 2.23% of Pakistan's landmass, these forests emerge as guardians of green growth, offering an array of benefits that significantly impact the health and sustainability of our nation. This exploration unveils the profound influence of forests on physical health, including improved air quality, enhanced respiratory health, and the therapeutic effects of forest therapy. Moreover, the article delves into the positive impact of forests on mental health, reducing stress, anxiety, and depression while promoting overall well-being. Intriguingly, Pakistan's forests also have a role in healthcare, contributing to traditional and modern medicine through forest-derived medicines. Additionally, the article highlights the importance of sustainable forest management and community engagement in conservation efforts to ensure that this symbiotic relationship thrives for generations to come. As we recognize how closely our health is connected to the forests around us, we invite readers to join us on a journey. This journey will show how this long-lasting partnership can make Pakistan greener and our lives healthier.